Unsymmetrically-1,3-disubstituted ferrocene-containing thermotropic liquid crystals: a new family of chiral metallomesogens - Deschenaux, Robert; Santiago, Julio (My University, 1994)
The synthesis and mesomorphic properties of the first family of unsym.-1,3-disubstituted ferrocene-contg. thermotropic liq. crystals are presented. The title compds. exhibited enantiotropic liq. cryst. phases (nematic and/or smectic A and smectic C phases) assocd. with large anisotropic domains. [on SciFinder(R)]
Keywords: liq crystal ferrocene unsym disubstituted